Factors to Predict the Financial Distress Condition of the Banking Listed in The Indonesia Stock Exchange - Kuncoro, Sarwo; Agustina, Linda (Universitas Negeri Semarang, 2017)
Penelitian ini dilakukan dengan tujuan untuk mengetahui pengaruh dari variabel yang diteliti dalam memprediksi probabilitas terjadinya financial distress sektor perbankan di Indonesia. Variabel dalam penelitian ini dipilih dengan pendekatan 5C, yang kemudian diproxykan menjadi GCG (Good Corporate Governance), ROA (Return on Asset), LDR (Loan Deposit Ratio),CAR (Capital Adequacy Ratio), TAG (Total Asset Growth), NPL (Non Performing Loans), PER (Price Eearning Ratio), PBV (Price Book Value Ratio). Populasi dari penelitian ini adalah bank yang terdaftar di Bursa Efek Indonesia periode tahun 2012-2014. Pengambilan sampel dilakukan dengan menggunakan teknik purposive sampling, hingga diperoleh 25 peristiwa financial distress pada periode penelitian. Penelitian ini menggunakan analisis regresi logistik untuk menguji pengaruh variabel independen terhadap variabel dependen. Hasil penelitian menunjukkan variabel return on asset dan capital adequacy ratio berpengaruh negatif terhadap probabilitas financial distress, sedangkan good corporate governance, loan deposit ratio, total asset growth, non performing loans, price earning ratio, dan price book value ratio tidak berpengaruh secara signifikan terhadap probabilitas financial distress. This research aims to analyze the effect of the variabels to predict Indonesian Banks’s financial distress. Those variabel was chosen by using 5C methods. The 5C methods consist of GCG (Good Corporate Governance), ROA (Return on Asset), LDR (Loan Deposit Ratio),CAR (Capital Adequacy Ratio), TAG (Total Asset Growth), NPL (Non Performing Loans), PER (Price Eearning Ratio), PBV (Price Book Value Ratio). The population of this study was all banks listed in Indonesia Stock Exchange (ISX) in 2012-2014. Sampling is done by using purposive sampling method, until founded that was 25 financial distress phenomena that happens in that periods.This study used logistic regression analysis for testing the influence of independent variables on dependent variable. The results of this study showed return on asset and capital adequacy ratio negative significantly influence to the probability of financial distress, meanwhile good corporate governance, loan deposit ratio, total asset growth, non performing loans, price earning ratio, and price book value ratio had no significantly influence to to the probability of financial distress. Keyword: Financial distress, 5C methods, Financial ratio, bank.